Evaluation of the relationship between MAOA-uVNTR gene polymorphism and impulsivity, anger, temperament and personality traits in healthy male subjects - Kaya, Hasan; Bolat Kaya, Ozlem; Civan Kahve, Aybeniz; Dilbaz, Nesrin (Annals of Medical Research, 2021)
Aim: Serotonergic activity in the central nervous system negatively correlates with personality traits associated with aggression, impulsivity and anger. MAOA is involved in the catabolism of serotonin and norepinephrine, so the gene encoding MAOA is a candidate gene for aggression-related behavior. It is thought that MAOA genetic variants affect the MAOA activity at different degrees, leading to behavioral changes as a result of a decrease in enzyme activity. The aim of this study is investigating the possible relationship between the MAOA-uVNTR polymorphism genotypes and aggression, anger, impulsivity, temperament-character traits in healthy male subjects. Materials and Methods: 101 Turkish healthy male subjects were included in the study. The participants were given scales to evaluate impulsivity, temperament and character traits, anger and aggression levels. MAOA-uVNTR polymorphism was examined with a sample taken from peripheral blood.Results: A total of 101 people, 33.6% had low-activity allele and 66.4% had high-activity allele of MAOA gene. There was no significant relationship between the temperament-character traits of the participants and MAOA-uVNTR polymorphism. Impulsivity scales were higher in the low-activity allele group, which was statistically significant in terms of motor impulsivity (p = 0.007), non-planning impulsivity (p = 0.031) and total scores (p = 0.029). Conclusion: The low-activity allele of MAOA gene may be a marker for impulsivity. This requires both repetitive studies with healthy controls in the Turkish population and studies in different cultures.
Keywords: Character traits; impulsivity; MAOA polymorphism; MAOA-uVNTR; temperament